Effect of nitrogen fertilisation on the amino acid digestibility of different triticale genotypes in caecectomised laying hens. (19th April 2016) - Siegert, Wolfgang; Boguhn, Jeannette; Maurer, Hans Peter; Weiss, Jochen; Zuber, Tobias; Möhring, Jens; Rodehutscord, Markus
Abstract: BACKGROUND: The influence of nitrogen fertilisation and genotype on the amino acid (AA) digestibility of triticale grain was investigated in caecectomised laying hens. Three genotypes, Grenado, EAW6002 and Lasko, were cultivated with and without nitrogen fertilisation at the end of the heading stage. The six triticale variants as well as a basal diet were each used to feed seven laying hens in a 7 × 7 Latin square design. RESULTS: Nitrogen fertilisation influenced the digestibility of Cys, Glu, Phe and Ser in some triticale genotypes and reduced Ala, Ile, Lys, Met and Val digestibility in all genotypes ( P < 0.05). Nitrogen fertilisation increased the concentration of all AAs in the grain. Consequently, the concentration of digestible AAs in the grains was increased for most AAs upon nitrogen fertilisation. Overall, Lys had the lowest digestibility, whereas that of Glu and Pro was the highest. For the triticale genotypes, the level of AA digestibility was highest for EAW6002 followed by Lasko and Grenado, with significant differences ( P < 0.05) between genotypes for some but not all AAs. CONCLUSION: The results indicated that the accuracy of the digestible AA supply for hen feeding might benefit from considering fertilisation and genotype‐specific digestibility data in feed formulation. © 2016 Society of Chemical Industry